Characteristics and Frequency of Pediatric Inflammatory Bowel Disease-Associated Pancreatitis: A Japanese Nationwide Survey. Issue 1 (24th February 2022) - Hosoi, Kenji; Minowa, Kei; Suzuki, Mitsuyoshi; Kudo, Takahiro; Ohtsuka, Yoshikazu; Tomomasa, Takeshi; Tajiri, Hitoshi; Ishige, Takashi; Yamada, Hiroyuki; Arai, Katsuhiro; Yoden, Atsushi; Ushijima, Kosuke; et al.
Abstract : Objective: Acute pancreatitis (AP) develops in approximately 2% of patients with the diagnosis of inflammatory bowel disease (IBD), but the characteristics and frequency of childhood-onset IBD-associated AP in Japan have not been studied. The present study aimed to clarify the characteristics of IBD-associated AP in Japan. Methods: A nationwide survey of pediatric patients with IBD (age, <17 years) was conducted from December 2012 to March 2013 at 683 hospitals and medical centers in Japan. A secondary survey was also sent to the centers with the target patients to evaluate their characteristics. Results: The response rate to the first part of the survey was 61.2% (n = 418). In total, 871 patients with Crohn disease and 1671 patients with ulcerative colitis were enrolled. The second part of the survey found that 11 (1.3%) patients with Crohn disease and 23 (1.4%) patients with ulcerative colitis experienced IBD-associated AP caused by medication (n = 18, 53%), a primary disease (n = 11, 32%), autoimmune pancreatitis (n = 1, 3%), or an anatomical abnormality (n = 1, 3%). All the patients had only mild AP. Conclusions: IBD-associated AP was not very frequent and was generally mild. The major cause of the pancreatitis was the medication used to treat the IBD.